2020
DOI: 10.1038/s41598-020-65251-2
|View full text |Cite
|
Sign up to set email alerts
|

Independent and combined effects of age, body mass index and gestational weight gain on the risk of gestational diabetes mellitus

Abstract: This study aimed to identify the independent and combined effects of age, BMI at first prenatal visit and GWG on the risk of GDM. A retrospective cohort study of 1,951 pregnant women in Seremban district, Negeri Sembilan, Malaysia. GDM was defined as fasting plasma glucose (FPG) ≥5.6 mmol/l and/or 2-hour postprandial plasma glucose (2hPPG) ≥7.8 mmol/l. A higher percentage of women with GDM had 2 risk factors (29.0%) or >2 risk factors (8.6%) compared to non-GDM women (2 risk factors: 25.5%; >2 risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 41 publications
8
67
1
Order By: Relevance
“…A very recent retrospective cohort study of Malaysian women (SECOST) showed that overweight or obesity and age ≥ 35 years were associated with a 2.45-fold higher risk of GDM [3]. Excessive gestational weight gain during the second trimester by these women further increased their risk of developing GDM [4]. Moreover, other factors such as unhealthy nutritional habits (so-called "western diet" composed, to a large extent, of highly processed and calorie-rich foods, with low amounts of vegetables) and low physical activity are also significant risk factors for developing GDM [5,6].…”
Section: Gestational Diabetes Mellitus-a Brief Description Of Gdm Epimentioning
confidence: 99%
“…A very recent retrospective cohort study of Malaysian women (SECOST) showed that overweight or obesity and age ≥ 35 years were associated with a 2.45-fold higher risk of GDM [3]. Excessive gestational weight gain during the second trimester by these women further increased their risk of developing GDM [4]. Moreover, other factors such as unhealthy nutritional habits (so-called "western diet" composed, to a large extent, of highly processed and calorie-rich foods, with low amounts of vegetables) and low physical activity are also significant risk factors for developing GDM [5,6].…”
Section: Gestational Diabetes Mellitus-a Brief Description Of Gdm Epimentioning
confidence: 99%
“…Finally, the influence of age and month on GDM and PIH would be discussed. The age might be a notable factor on GDM 23 . Fig.…”
Section: Discussionmentioning
confidence: 99%
“…More severely overweight or obese women with GDM might have benefited even more from the intervention. Since women with an older maternal age and pregestational overweight/obesity are generally more at risk of GDM [ 18 ], including these in further research is of particular interest.…”
Section: Discussionmentioning
confidence: 99%